Impact of sport specific and generic visual stimulus on a reactive agility test while carrying a rugby ball - Meir, R.; Holding, R.; Hetherington, J.; Rolfe, M. (Journal of Australian Strength and Conditioning, 2013)
One of the essential physical skills attributed to a successful rugby league player is agility (5). Verstegen and Marcello (15) have suggested that agility is a quality that supports the ability to react to a stimulus, start quickly and efficiently, move in the correct direction, and be ready to change direction or stop quickly to make a play in a fast, smooth, efficient, and repeatable manner. Sheppard and Young (12) suggest that a more comprehensive definition of agility should include the physical demands (strength and conditioning), cognitive processes (motor learning) and technical skills (biomechanics) involved in these types of movements. They also propose that agility be defined as: a rapid whole body movement with change of velocity or direction in response to a stimulus. Sheppard and Young (12) identify two broad types of agility. These are: i) reactive agility, that includes physical and cognitive component that requires the athlete to react to some form of visual and or aural stimulus, and ii) change-of-direction speed (CODS), where the athlete negotiates a pre-planned movement requiring them to accelerate and decelerate while also changing direction. Reactive agility (RA) is the term used to distinguish between the traditional definition of agility and a more contemporary definition.